Penerapan model pembelajaran berbasis proyek (project-based learning) untuk meningkatkan keterampilan berpikir kreatif pada pembelajaran IPAS di Sekolah Dasar - Nur Anisah Ristiana; Peduk Rintayati Rintayati; Chumdari Chumdari Chumdari (Universitas Sebelas Maret, 2024)
The purpose of this study: (1) to explain the implementation of PjBL models in the context of IPAS (integrated science and social studies) learning of fourth grade elementary school Pajang IV Surakarta in the academic year 2022/2023. (2) to enhance creative thinking skills of fourth grade elementary school Pajang IV Surakarta. This research employs classroom action research approach. The subjects of this study were teacher and student of fourth grade elementary school Pajang IV Surakarta. The methods for gathering data included observation, interviews, documentation, and a test assessing creative thinking. Techniques for ensuring data validity involved the utilization of triangulation methods and source triangulation. The data analysis method consists of four stages: 1) data collection, 2) data reduction, 3) data presentation, and 4) drawing conclusions. The classroom action research procedure consists of planning, action, observation, and reflection. This research findings indicate that: (1) implementing the PjBL model to enhance creative thinking skills involves several steps, such as formulating fundamental questions, designing project plans, creating schedules, monitoring progress, assessing outcomes, and evaluating the overall experience. This improvement occurs over three instructional cycles, suggesting that the PjBL model can enhance creative thinking skills of fourth grade elementary school Pajang IV the academic year 2022/2023.